Relationship between rumen microbiota and pregnancy toxemia in ewes - Jiaxin Chen; Siwei Wang; Siwei Wang; Xuejiao Yin; Chunhui Duan; Jinhui Li; Yue-qin Liu; Yingjie Zhang (Frontiers in Veterinary Science, 2024)
IntroductionPregnancy toxemia (PT) is a nutritional metabolic disease of ewes in late pregnancy. This study aimed to reveal the relationship between rumen microbiota and PT.MethodsWe selected 10 healthy ewes (CON) and 10 pregnancy toxemia ewes (PT) at 135 days of gestation according to the blood β-hydroxybutyrate (BHBA), glucose (Glu) concentrations and clinical symptoms. Blood and rumen fluid were collected before morning feeding to determine serum biochemical indices and rumen fermentation parameters. Total DNA of rumen fluid was extracted and the V3-V4 regions of 16S rRNA were amplified by PCR for high-throughput sequencing.ResultsThe results showed that the serum concentrations of Glu, total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), uric acid (UA), creatinine (Cr), acetate, propionate, butyrate, and microbial crude protein (MCP) were decreased (p < 0.05) and the concentrations of BHBA, aspartate aminotransferase (AST), acetate to propionate ratio (A/P), and ammonia nitrogen (NH3-N)were higher (p < 0.05) in PT ewes than those in CON ewes. 16S rRNA analysis showed the differences of β-diversity were observed in rumen microbiota between CON and PT ewes. At the phylum level, the relative abundance of Bacteroidota and Proteobacteria were higher (p < 0.01), while Firmicutes was lower (p < 0.01) in PT ewes. At the genus level, the relative Prevotella, Butyrivibrio, Ruminococcus, Lachnospiraceae_AC2044_group, Lachnospiraceae_XPB1014_group, Lachnospiraceae_ND3007_group, and Oribacterium were lower (p < 0.01) in PT ewes. Meanwhile, the relative abundance of Oribacterium, Butyrivibrio, Ruminococcus, and Lachnospiraceae_AC2044_group were positively correlated (p < 0.01) with Glu, INS, acetate, propionate, and butyrate, and negatively correlated (p < 0.01) with BHBA, P, GC, AST, and A/P.DiscussionIn conclusion, the decrease of Oribacterium, Butyrivibrio, Ruminococcus, and Lachnospiraceae_AC2044_group in the rumen of PT ewes reduced the concentrations of volatile fatty acids (acetate, propionate, and butyrate) and serum Glu, and increased BHBA concentration, indicating that the differences in rumen bacteria genera were related to pregnancy toxemia of ewes.